Meeting the Challenges of Time: Exploring the Concept of Maqāşid Sharī’ah in the Thought of Jasser Auda - Rofi’i, Muhammad Arwani; Fata, Ahmad Khoirul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
This article discusses an overview of maqāşid sharī’ah in the thought of Jasser Auda, which forms the foundation of his approach to Islamic legal philosophy. Auda highlights the importance of understanding maqāşid sharī’ah as the primary goal of Islamic law. He argues that a deep understanding of maqāşid sharī’ah is necessary to produce just and welfare-oriented laws. In this perspective, Auda views Islamic law as an integrated system, where each part is interconnected and contributes to achieving the established goals. Auda also details that his systemic thinking encompasses concepts such as raḥmatan lil al-‘ālamīn (mercy to all creation) and maslahah (public interest), as guides for formulating laws that are responsive to the needs of society. This research concludes that Jasser Auda's thoughts on the philosophy of Islamic law, emphasizing maqāşid sharī’ah and Islamic law as an integral system, significantly contribute to understanding how Islamic law can function as a flexible and adaptive instrument in responding to the changes of time. This approach reinforces the idea that Islamic law is not static but can evolve according to its fundamental principles to achieve the welfare of the people and higher moral goals.